Social Responsibility as a Determinant in the Improvement of Organizational Competitiveness (Case Study) - Polek-Duraj, Kornelia (Olsztyn Economic Journal, 2017)
The level of involvement of Polish companies, especially micro, small and medium-sized ones, in their activities consistent with the concept of Corporate Social Responsibility is relatively small. On the one hand, it may be due to poor knowledge concerning this subject, especially about the benefits that derive from it, and what can be achieved (e.g. improved image, increased competitiveness, the ability to innovate). On the other hand, there is a need to bear, particularly in the beginning, the necessary costs, and this reimbursement is not immediately felt by the company. The aim of this article is to present a way of implementing the concept of Corporate Social Responsibility and its impact on improving the competitiveness of the audited company. The analysis was carried out at the largest wood processing plant in the Opole region.